Exploring the feasibility and acceptability of a recovery-focused group therapy intervention for adults with bipolar disorder: trial protocol. Issue 1 (31st January 2018) - Beck, Alison K; Baker, Amanda; Jones, Steven; Lobban, Fiona; Kay-Lambkin, Frances; Attia, John; Banfield, Michelle
Abstract : Introduction: Improving accessible, acceptable recovery-oriented service provision for people with bipolar disorder (BD) is an important priority. Mindfulness and acceptance-based cognitive and behavioural therapies (or 'third -wave' CBT) may prove fruitful due to the considerable overlap between these approaches and key features of personal recovery. Groups also confer therapeutic benefits consistent with personal recovery and may improve recovery-oriented service provision by adding another modality for accessing support. The primary objective of this trial is to explore the feasibility and acceptability of a new recovery-focused group therapy (RfGT) intervention for adults with BD. This is the first published feasibility assessment of a time-limited RfGTrecovery-focused group therapy intervention for BD. Methods/ analysis: This protocol describes an open feasibility study, utilising a pre-treatment design versus post- treatment design and nested qualitative evaluation. Participants will be recruited from the Central Coast region of New South Wales, Australia, from primary care providers, specialist mental health services, non-government organisations and via self-referral. The primary outcomes are feasibility and acceptability as indexed by recruitment, retention, intervention adherence, adverse events (if any) and detailed consumer feedback. Clinical outcomes and process measures will be assessed to inform future research. Primary outcome data will utiliseuse descriptive statistics (eg, summarizingsummarising recruitment, demographics, attendance, attrition and intervention adherence). Secondary outcomes will be assessed using repeated-measures analysis of covariance across all time points (including change, effect size and variability). Ethics and dissemination: Ethical approval has been granted by the Northern Sydney Local Health District HREChuman research ethics committee (HREC) (HREC/16/HAWKE/69) and The University of Newcastle HREC (H-2016–0107). The Ffindings will be used to improve the intervention per user needs and preferences, and inform what amendments and/or information are required before a follow-on trial would be possible. This study contributes to a growing body of innovative, recovery-oriented innovations of psychological treatments for adults with BD. Trial registration number: ACTRN12616000887471 ; Pre-results.